Uniciencia journal adopts the continuous publication model - Morales-López, Yuri (2021)
In 2018, the journal Uniciencia began an evaluation process on the number of papers received and evaluated, and the evaluation and editorial stages, with a view to assessing its periodicity in the light of current international requirements. Technical and administrative consultations were carried out with different instances such as the Faculty of Exact and Natural Sciences, the Vice-Rectory of Research, the Publications Department of the Universidad Nacional (UNA) in Costa Rica, the journal management consultancy of the UNA and other universities, as well as national and international accrediting agencies (Latindex, Redalyc, Scielo and Scopus Elsevier), among others. It is with great pleasure and pride that, as a result of this evaluation and the suggestions of the entities involved, on 27 November 2020 the Editorial Committee of the journal Uniciencia unanimously agreed to change the periodicity from biannual to a continuous publication model, starting with the publications of 2022. Thus, during 2021, a transition process will be carried out in which the current periodicity will be maintained. Adopting this model in a formal way is innovative and is a huge step and challenge for this publication. It is worth noting that the main objective is to manage a journal with greater impact and greater dissemination at national and international level, and whose purpose is to provide the most benefit to our readers, authors and, in general, to our society.